The Effect of Titanium Tetrafluoride Treatment and the CO2 Laser on Acid Resistance of Human Enamel - Azarsina, Mohadese; Panahandeh, Narges; Gholipour, Tahere; Namdari, Mahshid; Fekrazad, Reza (Journal of Lasers in Medical Sciences, 2019)
Introduction: Titanium tetrafluoride (TiF4) is deemed more effective than the previous fluoride compounds. To enhance the effect of the fluoride compounds, researchers have suggested their association with lasers, although there are conflicting results in this area. We evaluated the acid resistance of enamel after treatment with the CO2 laser and TiF4. Methods: Thirteen human premolar teeth were sectioned into 5 parts and each segment was assigned to a study group: co (control): without treatment, AF: enamel treatment with APF 1.23% for 4 minutes, TF: enamel treatment with TiF4 4% for 1 minute, TF-L: enamel treatment with TiF4 4% and then the CO2 laser (Peak power: 1 W, pulse duration: 10 ms, interval time: 500 ms, Beam spot size: 0.2 mm, distance: 2 cm), L-TF: enamel treatment with the CO2 laser and then TiF4 4%. Each sample was kept for 7 days in acidic solution of hydroxyethyl cellulose at pH=4.5, and the amount of the calcium ion released in the solution was measured by atomic absorption spectrometry. Data were analyzed by ANOVA and Bonferroni tests. The significance level was set at 0.05. Results: The average concentration of the calcium ion released in acidic solution was 197.46, 153.30, 99.23, 61.23, 55.46 ppm in the groups respectively. There was a significant difference between the study groups (P < 0.0001). Only the difference between TF-L and L-TF was not significant (P > 0.05). Conclusion: The loss of calcium from the enamel samples in the groups treated with a combination of the laser and TiF4 was significantly lower than the groups treated with fluoride alone, or the control group. It did not make a significant difference whether the CO2 laser was applied before or after TiF4.